2023
DOI: 10.1098/rstb.2022.0286
|View full text |Cite
|
Sign up to set email alerts
|

Functional identification of hot-spot mutations in cardiac calcium channel genes associated with the J wave syndromes

Abstract: J wave syndrome (JWS) is an inherited cardiac channelopathy associated with malignant ventricular arrhythmias and sudden cardiac death (SCD), which comprises early repolarization syndrome and Brugada syndrome. Here, we explore the association between variants in the L -type calcium channel gene subunits, α 1C ( CACNA1C ) and β2b ( CACNB2b ), and the JWS phenotype. Using next-generation genetic sequencing of 402 JWS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Third, similarly inward and depolarization-activated Cav1.2-mediated I Ca may initiate APs in the SAN and AVN besides prolonging atrial and ventricular phase 2 plateau activation. Their loss-of-function mutations, recently exemplified by CACNB2b-S143F and CACNA1C-G37R ( Zeng et al, 2023 ), resemble those involving Nav1.5 with pro-arrhythmic phenotypes accompanied by J wave syndromes ( Huang, 2017 ).…”
Section: Ion Channels Underlying Normal and Abnormal Rhythmic Activitymentioning
confidence: 99%
“…Third, similarly inward and depolarization-activated Cav1.2-mediated I Ca may initiate APs in the SAN and AVN besides prolonging atrial and ventricular phase 2 plateau activation. Their loss-of-function mutations, recently exemplified by CACNB2b-S143F and CACNA1C-G37R ( Zeng et al, 2023 ), resemble those involving Nav1.5 with pro-arrhythmic phenotypes accompanied by J wave syndromes ( Huang, 2017 ).…”
Section: Ion Channels Underlying Normal and Abnormal Rhythmic Activitymentioning
confidence: 99%
“…Notably, ERP exhibits a higher prevalence in physically active individuals, reported as reaching 33.9% [145]. Research on ERS consistently indicated a higher prevalence among men [153][154][155][156][157] and a younger age at diagnosis [154,156]. Identified independent risk factors associated with ERP include younger age, male gender, lower systolic blood pressure (SBP), shorter QRS duration, a shorter QTc interval, and hypothermia [145,146,151].…”
Section: Managementmentioning
confidence: 99%
“…Zeng et al . [ 72 ] associate variants of pro-arrhythmic J wave syndromes, also found with loss of Nav1.5 function, with loss of Ca 2+ channel function, CACNB2b-S143F and CACNA1C-G37R , mutations. AP repolarization ultimately restoring the resting potential is driven by a range of outward K + currents ( figure 2 b ) [ 23 , 73 ], for which a wide range of new K + channel subtypes have been described [ 73 77 ].…”
Section: Ion Channels Contributing To Cardiomyocyte Surface Membrane ...mentioning
confidence: 99%